BAURAN PEMASARAN INDUSTRI KREATIF SUB SEKTOR KRIYA DI KAMPUNG RAJA PRAILIU - Ngenju, Marvilinus Keba; Situmorang, Tumpal P (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2024)
The purpose of this study is to analyze the 4p marketing mix applied to ikat weaving in Kambera District, especially in Raja Prailiu Village. The informant of this research is the owner of a ikat weaving business in Raja Prailiu village as many as 4 informants The data analysis technique used is qualitative descriptive. The results of the study concluded that: There are two types of ikat woven fabric products in Prailiu king's village, namely kawuru cloth and kombu fabric, using natural dyes and shop dyes or wantek, with motifs of horse, chicken, patola and ana mahang motifs. While the price of ikat woven fabric is determined by the type of fabric, type of dyeing, motif / image and fabric size. With a place that is easy to reach, and is in the center of the crowd, which is located on the edge of the city. With promotional media using social media using cellphones in the form of Facebook (Fb) and WhatsApp (WA). And direct promotion or word of mouth.